The importance of using financial engineering to form a hedging portfolio from the entrance to call options approach: “ Application in a sample of iraqi industrial shareholding companies ” - Ismael, Meena; Abdullah, Bassam (Humanities Journal of University of Zakho, 2023)
The study focused on measuring and evaluating a portfolio to hedge risks using the fair theoretical values of pricing call options for a sample of Iraqi industrial companies because options are ways to manage risks resulting from investment transactions in common stocks by reading financial phenomena to achieve stability in the dual binary of return and investment risks in stocks. The research also sought to give empirical evidence for pricing the value of call options using the binomial model, as well as to provide tests to clarify the process of assessing the hedging portfolio based on the theses of the literature in this subject. In this study, call options were priced for a sample of 12 industrial businesses listed in the Iraqi market that were chosen at random for the period from the beginning of 2021 to the end of 2021 using daily stock prices in order to evaluate the study hypotheses. The pricing of call options was established by creating a link between changes in the portfolio's value and the numerous arbitrage opportunities that were available. The study's findings led to the conclusion that developing a hedging portfolio based on the fair value pricing outputs of options can assist decrease the investment risks encountered by industrial sector investment portfolios, which comprised the study sample. Considering what the purchasing or selling price of a specific option symbolizes in the financial market, the study reveals that the basis of the whole investing process is to take advantage of these options for all relevant parties in the financial market as an informative signal. This is because the summary includes the interplay of several distinct variables, including the execution price and contract period. It accurately depicts the fair value of the components that affect the price of the option, and hence the price of the stock.